Pemberdayaan Komunitas Belajar Musik dan Bahasa melalui Media Pembelajaran Informal di Bandar Lampung - Riyan Hidayatullah; Sumarti; Prisma Tejapermana; Muharsyam Dwi Anantama; Mar'an, Desy Awal (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This training program aims to explore and provide guidance on community empowerment through music and language learning communities via informal learning media in Bandar Lampung. In the context of informal education, learning media plays a critical role in enhancing the skills and knowledge of community members without being bound by formal curricula. This empowerment program employs various interactive methods that integrate music and language as tools to enrich the learning process. By leveraging digital technology and group activities, the community is provided with access to diverse learning materials that can enhance their language skills and musical appreciation. The method used is a participatory approach, involving community members (students) in the planning and implementation of activities. The results indicate that the use of informal learning media, particularly through a group approach, is effective in fostering active participation and skill development among community members. Additionally, this approach has successfully strengthened social bonds and collaboration among community members. This study concludes that community empowerment through informal learning media is a promising strategy to optimize the learning process and enhance the quality of education outside formal institutions.